Stability of stationary solutions to 2D Boussinesq equations with partial dissipation on a flat strip. (February 2022) - Chen, Dongxiang; Li, Xiaoli
Abstract: The global existence and stability of perturbation of 2D Boussinesq equations with partial dissipation near hydrostatic equilibrium on a flat strip Ω ≔ T × [ 0, 1 ] are obtained with the help of a time-weight energy estimate. Meanwhile, we also establish the explicit decay rates of the solution of 2D Boussinesq equations.